VARIASI JENIS BAHAN BAKAR PADA PENGASAPAN IKAN BANDENG (Chanos-chanos Forskal ) MENGGUNAKAN ALAT PENGASAPAN TIPE KABINET - Ratna Ratna; Safrida Safrida; Yulinar Yulinar (Universitas Syiah Kuala, 2011)
The milkfish represent one of the high commodities of protein and consumed many by society in Aceh. This research aim at to know influence of fuel type to quality of milkfish use appliance smoked of cabinet type. Time needed to degrade water concentration around 15% at coconut shell of coconut fuel is 4 hours, representing lower concentrate rate of water of smoked milkfish. Protein rate in milkfish smoked use fuel coconut shell is 32,75%, chaff of rice 27,18%, coconut coir 37,70%, and wood 27,09%. Fat rate of milkfish smoked use coconut shell of coconut fuel is 7,84%, chaff of rice 9,18%, coconut coir 7,13%, and wood 8,85%. In the test of organoleptik shell of coconut and coconut coir shows fish product which prefer either from form, colour, aroma and feel.